Early response of the gut microbiome and serum metabolites to Cheonggukjang intake in healthy Korean subjects. (February 2023) - Song, Eun-Ji; Kim, Min Jung; Jung, Chang Hwa; Chung, Won-Hyong; Nam, Young-Do; Lim, Mi Young
Graphical abstract: Highlights: We examined the effects of Cheonggukjang (CKJ) on gut microbes and serum metabolites. The gut microbiota was clustered into three enterotypes. CKJ supplementation resulted in different acute responses depending on the enterotype. Results support the importance of personalized nutrition guidance based on enterotype. Abstract: Cheonggukjang (CKJ) is a traditional fermented soybean food in Korea. The human gut microbiota varies among individuals, which can differentially affect food digestion, absorption, and reactivity. We aimed to examine associations between the gut microbial composition and isoflavone metabolites after CKJ supplementation. Feces were collected from 48 healthy Korean individuals, before and after CKJ supplementation, for gut microbial composition analyses. The gut microbiota was clustered into three enterotypes, represented by Bacteroides, Prevotella, and Ruminococcaceae. Differences were observed in the compositional changes in the gut microbiota and isoflavone-metabolite profiles after CKJ supplementation, depending on the enterotype. Changes in the microbial community were more pronounced in the Ruminococcaceae-rich enterotype, and the 5-hydroxy equol level was significantly higher in the Prevotella -rich enterotype than in the other enterotypes. CKJ supplementation resulted in different acute responses depending on the enterotype. The results further support the importance of personalized nutrition guidance based on an individual's gut microbial composition.